Reflective journals in service learning: a window into assessing learning and change in students' attitudes - R W Joubert; A T Hargreaves (The Journal for Transdisciplinary Research in Southern Africa, 2009)
As part of the curriculum for Community Based Rehabilitation, final year students from the School of Audiology, Occupational Therapy and Speech-Language Pathology are involved in service learning projects in a semi rural area in KwaZulu-Natal. The project runs one day a week from February to October and at the end of each day students submit a journal in which they reflect on each days activities and their learning experiences. The researchers used these journals as a source of data for determining learning and attitude change in students over the entire period of the practical. Method : 12 journals were randomly selected from over a period of 5 years and including students from all three disciplines. Content analysis was done to determine changing learning and attitudinal patterns over the 7 month period of the practical. The results revealed a rich pattern of emotional experiences coupled with positive attitudinal change and suggest a valuable source of evaluating learning progress in students.